LOD for Architectural Heritage: BIM Modeling for the Solimene Factory - Adriana Rossi; Umberto Palmieri (Diségno)
The authors created a BIM model of a significant portion of the Solimene ceramic factory (Vietri, Salerno) based on an unstructured model obtained with phase-shift 3D laser scanning. The components, referred to standardized levels of development (LOD), are placed at the origin of a shared and interoperable workflow, suitable for comparing documents and models for design purposes and dissemination of architectural heritage.